GIS based suitability analysis for siting petrol filling stations in Zaria Local Government, Kaduna State Nigeria - Abdulkadir, Aliyu Bello (2022)
This study analyzed and assessed the Suitable site and distribution of petrol filling stations in Zaria Local Government based on the development standards set by Department of Petroleum Resource (DPR). The research used field surveys, GPS, remote sensing, and geographic information system (GIS) tools to locate and map the existing petrol filling station stations. The study located and mapped 56 petrol stations in the area. All analyses and mapping were carried out using ArcGIS 10.7 after the field data were processed in an Excel spreadsheet. A Multi Criteria Decision Analysis was performed in the research using weighted overlay tools. The distribution of the stations was calculated using the nearest neighbor method. The analysis clearly showed that the distribution of the petrol filling stations in the study area are clustered. The distances between petrol filling stations, the location of filling stations on the highway and the distances between filling stations to the nearest features were determined using the same technique. According to the survey, the listed petrol stations were all spread out along the highway on both sides. Additionally, it showed that only 3 of 56 gas stations met all of the development guidelines. The results of this study have also demonstrated the value of geospatial tools for managing and monitoring development in the built environment. Building ability to use the technology should be prioritized by relevant governmental agencies example Department of Petroleum Resource (DPR). In order to prevent haphazardly siting of petrol filling stations in the area, the study recommended regular monitoring by the Department of Petroleum Resource (DPR) to assure complete compliance with the rules. Lastly, there should be proper planning in order to handle future road expansions.